Traditional ecological knowledge of mangrove wood use on the Brazilian Amazon coast - Galvão, Madson Lucas; Rodrigues, Tatiane Nascimento Medeiros; Santos, Iedo Souza; Fernandes, Marcus Emanuel Barroncas (Ethnobiology and Conservation, 2024)
Traditional ecological knowledge (TEK) has been widely used and valued as a reliable source of information in the development of research on the various uses of the forest. Here, the socio-environmental factors that affect the traditional knowledge of extractivists about the uses of mangrove wood in an estuarine-coastal community in the Brazilian Amazon region were analyzed. The grouping of words evoked in semi-structured interviews with 108 local informants highlighted the lexicons that best express the use of mangrove wood. Factorial correspondence analysis was used to assess the intersection between words and age groups, helping to indicate respondents’ TEK of these uses. Most respondents say that wood is used for domestic (family) purposes, mainly charcoal and weir, and that these purposes and applications were taught by the older generation of the community. The traditional uses of the species Rhizophora mangle, Avicennia germinans, and Laguncularia racemosa have been validated by the scientific literature through their technological properties. From this validation, a relevant contribution is to include the participation of users in intervention processes by using their TEK, making the planning process of preventive conservation strategies and management proposals more efficient, promoting the reduction of a future advance deforestation in this region. Likewise, such information is relevant to guide the social actors involved in the implementation of public policies, favouring the creation of new alternatives and solutions for better management and use of wood resources in mangrove areas.